Legalitas Penyaluran Harta Zakat dan Bantuan Non Muslim sebagai Dana Wakaf pada Bank Wakaf Mikro Perspektif Fikih - Bakhrul Huda (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
The government project by establishing a Micro Waqf Bank by cooperating with pesantren to boost the lower-level economy is a relevant program for the lower classes. There are already about 20 standing banks that have been inaugurated by the government spreading in the land of Java until now. Micro Waqf Bank whose capital is used as waqf funds are funded by Laznas BSM, where Laznas main function is collector of zakat property. From here it is feared there is a zakat treasure participated donated for the establishment of Micro Waqf Bank, meaning that the treasure of zakat is made waqf treasure. Then if Laznas BSM in financing the establishment of Micro Waqf Bank turned out to use infaq funds and non-Muslim donations, then how legality of Islamic jurisprudence in that case. In this study the authors want to research and describe the opinion of fiqh scholars related to the legality of zakat property which is used as waqf property and donation of non-Muslims to be made waqf property in Micro Waqf Bank which has been going on today. And the conclusion of this study is that zakat property is not allowed to become a waqf capital in the Micro Waqf Bank by majority of scholars while non-Muslim donation can be used as waqf property in Micro Waqf Bank with existing provisions.